Onlineprylar : Ett egenutvecklat annonseringsgränssnitt med användare i fokus - Danial, Dany (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2021)
When it comes to selling both new and used goods and services, it is quite common for people touse various online sales platforms. For those people who have a stressful everyday life with jobs,errands and responsibilities in the home, an advertising interface that is quick and easy to use isneeded. The advantage of this is that it can be used at any time and it also ensures that you do notlose much time and attention from the daily activities. This is a degree project in bachelorprogramme in Industrial Design engineering at Luleå University of Technology and is about,through the involvement of users, creating and developing an advertising interface that is bothuseful and user-friendly. To be sure that the users are in focus, a user-centered design process is used that contains the subprocesses;Project Planning, Context of Use, Create Ideas and Prototype Concepts. By usingdifferent creative and user-centered methods, such as Personas and Think aloud, different userneeds have been described. Then Brainstorming is used to generate a lot of ideas for partialsolutions based on the five components of an interface; layout, shape, color, object and function.Scamper is then used to combine all the sub-solutions based on the components, into a completesolution. To create a whole picture of the complete solution, it has first been sketched, thenvisualized and finally web-programmed a clickable prototype. Through user tests of the clickable prototype, the results have clearly pointed out that it fulfills thepurpose and goal of the degree project, i.e. to create, develop and deliver a useful and user-friendlyclickable prototype. När det kommer till försäljning av både nya och begagnade varor samt tjänster så är det ganskavanligt att människor använder sig av olika säljplattformar på nätet. För de människor som har enstressad vardag med jobb, ärenden samt ansvar i hemmet så behövs ett annonseringsgränssnitt somgår snabbt och enkelt att använda. Fördelen med detta är att det kan användas när som helst och attdet också ser ...